Epidemiological and clinical characteristics and maternal-perinatal outcomes in pregnant women with COVID-19 in two hospitals in Huaraz, 2020 - Rodriguez-Figueroa, Ada (2023)
Introduction: Pregnancy generates functional and structural modifications that increase vulnerability to infection by pathogens that invade the respiratory tract and other systems, including COVID-19, with the possibility of causing severe pneumonia with hypoxic states, it needs to be studied, characterized and assess your results.Objective: To determine the epidemiological and clinical characteristics and maternal-perinatal outcomes in pregnant women with COVID-19 in two Hospitals in Huaraz 2020.Materials and Methods: Basic, descriptive and retrospective research, with a non-experimental and cross-sectional design, in a sample of 234 cases of pregnant women with COVID-19 from two hospitals in Huaraz during the year 2020; the study variable was: epidemiological, clinical characteristics and maternal perinatal results; the documentary technique was used, the instrument was the data collection form and the statistical analysis was usedunivariate descriptive.Results: The most outstanding characteristics of the pregnant women with COVID-19 were: a) epidemiological: age from 19 to 34 years (69.5%), urban origin (70.3%), cohabitants (71.6%), with anemia/urinary tract infection (UTI) (41.5%), 24 weeks or more of gestation (96.8%) and multiparous (51.2%). b) Clinics: symptomatic (63.5%), complicated with mild pneumonia (92.6%) and received antibiotics and analgesics (62.1%). c) Perinatal maternal outcomes: preterm (12.6%), vaginal delivery (69.5%), favorable clinical evolution (97.9%), did not enter careintensive (98.6%), hospitalized from 0 to 3 days (82.5%), male neonates (52.6%), APGAR greater than 6 (90.5%), with normal weight (82.8 %), were isolated (95.1%), there were no cases of maternal mortality (0.0%) and 20 cases of neonatal mortality (7.0%).Conclusions: Pregnant women infected with COVID-19 present various epidemiological and clinical characteristics, such as the marked frequency of anemia and UTI, with symptomatic pictures, complicated by mild pneumonia, among others; Maternal-perinatal results showed zero maternal mortality, but with an alarming number of neonatal deaths that require further study.